Images of Love, Womanhood and Childhood in the Poems by Anna Swir and Wislawa Szymborska - Bela, Teresa (Armenian Folia Anglistika, 2008)
The article reveals the similarities and differences in the English translations of the poems by two Polish women-writers on the same topic – A. Swir and W. Szymborska. The analysis rests on comparison and contrast. Both writers present the post-war reality in Poland using different methods of description, different poetic images which help demonstrate the authors’ individual attitude to female issues.